An experimental investigation of forming load and side-wall thickness obtained by a new deep drawing die - Savas, Vedat; Secgin, Omer (Springer France, 2010)
Deep drawing is an important process used for producing cups from sheet metal in large quantities. The deep drawing process is affected by many variables such as blank shape, punch and die radii, material's formability characteristics, and many more. In order to obtain optimal process parameters with regard to part geometry, the blank and die geometry are particularly important factors. In this study, we investigated the effects of blank holder and die shapes, using six different blank holder and die shapes. We measured the distribution of blank holder force (BHF), the forming load at different drawing depths as well as thickness reduction of cup wall thickness for each set of die and punch geometries. The experimental study shows that the angle of blank and die surface influence the forming load and blank holder force distribution. Deep drawing dies with matrix and blank holder angle designed in this study provided deep drawing ratios that are about 25 % larger than those that usually can be obtained by a conventional die.
Keywords: Deep drawing ratio; Blank and punch force; Angle of blank holder and die